2015
DOI: 10.4038/tar.v25i4.8054
|View full text |Cite
|
Sign up to set email alerts
|

Use of information and communication technology (ICT) by extension officers of the tea small holdings development authority of Sri Lanka

Abstract: The use of advanced technologies for information dissemination in the tea industry is crucial as tea (Cameliasinensis (L.)Kuntze.) is one of the major foreign exchange earning agribusinesses in Sri Lanka. This study contributes to understand the present status of information needs, use of information and communication technology (ICT) and the contributory factors for use of ICT among extension workers serving the tea small holders. A survey was conducted with a randomly selected representative sample of 101 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 6 publications
3
11
0
Order By: Relevance
“…This is in line with research by Seepersad [21] who reported that cell phones are fairly common among extension employees in Trinidad and Tobago. Samansiri and Wanigasundera [20] found similar results. Majority of the respondents (87.5%) uses internet to transfer necessary information while 52.5% and 75.0% of the respondents uses video chatting and multimedia projector for transferring agricultural information, respectively.…”
Section: Use Of Ict Toolssupporting
confidence: 54%
“…This is in line with research by Seepersad [21] who reported that cell phones are fairly common among extension employees in Trinidad and Tobago. Samansiri and Wanigasundera [20] found similar results. Majority of the respondents (87.5%) uses internet to transfer necessary information while 52.5% and 75.0% of the respondents uses video chatting and multimedia projector for transferring agricultural information, respectively.…”
Section: Use Of Ict Toolssupporting
confidence: 54%
“…As with age, it can be inferred that personnel with lesser experience (assumed to be younger) have more inclination toward using ICT than the more experienced (older) ones. These results echo findings from studies conducted by Salau and Saingbe (2008); Meera and Sain (2010); Adetumbi, Olaniyi, and Adewale (2013); and Samansiri and Wanigasundera (2014). These revealed significant association between sex, age, education, and work experience of the personnel from agricultural extension organizations and their ICT usage characteristics.…”
Section: Prevalence Of Significant Association Between Demographic Characteristics Of Personnel Their Pattern Of Ict Usagesupporting
confidence: 85%
“…It can be surmised from these results that older and more experienced extension personnel with rich educational qualifications are reluctant to use ICT. However, earlier studies (Salau and Saingbe 2008;Meera and Sain 2010;Adetumbi et al 2013;Samansiri and Wanigasundera 2014) show that with increase in age and decrease in educational qualifications, the use of ICT in the workplace diminishes.…”
Section: Pattern Of Ict Usage Of Personnel From Agricultural Extension Organizationsmentioning
confidence: 95%
“…Thus, improving awareness of modern ICT tools may promote their use by both public and private extension officers. Samansiri and Wanigasundera (2014) also found a correlation between awareness and use of ICT, but no significant relationship between age and use of mobile phones. Tata and McNamara (2016) found that gender, age, education and access to Internet have some impact on challenges in using ICT by extension officers.…”
Section: Determinants Of Use Of Ict Tools Among Respondentsmentioning
confidence: 80%